Ecological niche modeling and factors determining the range of the wood mouse Sylvaemus sylvaticus (Linnaeus, 1758) - Mezhzherin, S.V.; Tytar, V.M.; Tereshchenko, V.O. (Доповіді НАН України, 2023)
Ecological niche modeling of the wood mouse Sylvaemus sylvaticus, using machine learning method and a space of 35 bioclimatic factors, revealed that the most favorable conditions for this species are found in Western Europe. Th e primary core distribution areas are concentrated there, with the probability of encountering this species in habitable landscapes reaching 60 %. In contrast, the bioclimatic conditions of Eastern Europe are pessimistic: the habitat of the species is significantly fragmented, the cores are absent, the probability of encounters does not exceed 40 %, most often being less than 10 percentiles. It is evident that among the bioclimatic factors, climate continentality plays a central role, indirectly influencing the eastern border of the S. s. sylvaticus range and shaping specific vegetation types. Direct effects of individual factors and interspecies relations are possible and do occur, limiting the species’ eastern expansion, primarily in the southern part of its eastern range borde.